2021
DOI: 10.1002/cbdv.202001020
|View full text |Cite
|
Sign up to set email alerts
|

Marine Natural Products: The Important Resource of Biological Insecticide

Abstract: Due to the unique environmental conditions and vast territory, marine habitat breeds more abundant biological resources than terrestrial environment. Massive marine biological species provide valuable resources for obtaining a large number of natural products with diverse structure and excellent activity. In recent years, new breakthroughs have been made in the application of marine natural products in drug development. In addition, the use of marine natural products to develop insecticides and other pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 113 publications
(107 reference statements)
0
11
0
4
Order By: Relevance
“…In pursuit of an alternative to these endangered natural resources, many scientists have diverted their attention towards the utilization of the marine environment having the probability of great commercial exploitation globally (Song et al 2021 ). The marine environment has an abundant resource of natural products with diverse action in regards to antibacterial, antifungal, antiviral, anti-parasitic, anti-tumour, anti-inflammatory, antioxidant, and immunomodulatory activities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pursuit of an alternative to these endangered natural resources, many scientists have diverted their attention towards the utilization of the marine environment having the probability of great commercial exploitation globally (Song et al 2021 ). The marine environment has an abundant resource of natural products with diverse action in regards to antibacterial, antifungal, antiviral, anti-parasitic, anti-tumour, anti-inflammatory, antioxidant, and immunomodulatory activities.…”
Section: Introductionmentioning
confidence: 99%
“…The algae found in the marine environment have an abundant source of natural products which could be exploited for therapeutics and other applications. These algae are found in both forms i.e., prokaryotic, and eukaryotic with a wide variety of habitation ranging from shallow to coastal, and backwater (Bhalodia and Shukla 2011 ; Song et al 2021 ). Many scientific reports have shown that compounds isolated from these marine organisms have both in vitro and in vivo activities against the gram-positive and gram-negative microbes (Pina-Pérez et al 2017 ; Ancheeva et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the vast marine environment, marine organisms are regarded as the most abundant source of bioactive natural products, and the compounds obtained from them reflect their biological diversity [ 19 ]. In the past few years, with the full exploitation of other resources, the marine environment has generated a new research field, and many drugs from marine natural products have entered clinical trials [ 20 ]. Recent studies have pointed out that 170 marine natural products and their synthetic analogues have strong anticancer biological activities [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unique marine environments include the deep sea, Arctic and Antarctic zones, and symbiotic environments, making marine-derived organisms significantly different from terrestrial organisms. Thus, it would be reasonable to presume that marine organisms have diversified structures and functions [2]. Most marine organisms are considered an important resource for pharmaceutical and other economically useful applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%